"An Econometric Analysis of the Determinants of Profitability and Efficiency within UK Commercial Banks Post Financial Crisis" - Rajhi, Mohamed (2016)
This thesis investigates the determinants of profitability and efficiency within UK commercial banks post financial crisis: 2009-2015. The study closely examines the efficiency of UK commercial banks, the determinants of profitability and finally if the UK banking sector is experiencing economies or diseconomies of scale. The topic was chosen as there is a deficiency of studies post financial crisis that examine the UK banking sector; therefore a personal obligation to fill the void began, even more so as a great interest is shared in the subject topic. The methodology used is GMM (Generalised Methods of Moments) and SFA (Stochastic Frontier Analysis). The result show clear linkages with literature in numerous aspects. In looking at efficiency, the efficiency of the UK commercial banking sector was seen to score high at an average of 92.4% cost efficient. Furthermore, Lagged ROAA and CTI are the only two variables that are significant and affect profitability. Finally with the use of SFA it has been seen that the Banking sector is experiencing diseconomies of scale. These are the findings that the study has been aimed to discover and report.